PRINSIP ITIKAD BAIK DALAM PENDAFTARAN MEREK TYPE R MILIK HONDA MOTOR CO. LTD (STUDI PUTUSAN NOMOR 42/PDT.SUS-MEREK/2019/PN.NIAGA.JKT.PST) - Widya Ananda; Simona Bustani (Reformasi Hukum Trisakti, 2021)
The case of cancellation of registered trademark Handy Wijaya related to the element of bad faith in the registration of the trademark is similar in essence to the famous trademark of Honda Motor Co., Ltd. The problem is: how is the regulation of the principle of good faith in the registration of the TYPE R trademark owned by Honda Motor Co., Ltd. based on Law Number 20 of 2016 concerning trademarks and why the principle of good faith is not used as one of the legal considerations based on decision Number 42/Pdt.Sus-Merek/2019/PN.Niaga.Jkt Pusat. It is normative and qualitatively. The results of research, discussion and conclusion that the TYPE R Trademark owned by Handy Wijaya, proven to have similarities in essence with the Type R Trademark owned by Honda Motor Co., Ltd. regarding the shape, way of placement, way of writing, combination of elements or similarity of speech sounds which violates the principle of good faith in trademark registration in accordance with Law Number 20 of 2016 concerning Trademarks and Geographical Indications, where Handy Wijaya has been proven to register his trademark in bad faith which causes Handy Wijaya's TYPE R trademark to be canceled with all its consequences.